Evaluasi Kualitas Mutu Pelayanan Kefarmasian di Puskesmas Karangayung I dari Perspektif Pasien: Evaluation of the Quality of Pharmaceutical Services at Karangayung I Health Center from the Patient's Perspective - Amilia Krislinanda; Dyahariesti, Niken (Journal of Holistics and Health Sciences, 2025)
The level of patient satisfaction with the quality of a service can be used as an indicator of the quality of a health facility. The health center is the first referral health facility for the community to obtain health services, so the health center's quality must be guaranteed. One of them is the Karangayung I health center. This study aims to determine the level of satisfaction with outpatient pharmaceutical services at the Karangayung I Health Center from the patient's perspective. This study uses quantitative descriptive methods and uses a cross-sectional design. Using 95 respondents who meet the inclusion and exclusion criteria of the study. Data analysis uses univariate data analysis to determine the level of patient satisfaction with the quality of pharmaceutical services. The instrument used is a questionnaire. The results of the study showed the level of respondent satisfaction in the responsiveness dimension of 90.9%, the assurance dimension of 91.9%, the empathy dimension of 88.8%, the reliability dimension of 91.7% and the tangibles dimension of 86.8%. The quality of service at Karangayung Health Center is quite good, as seen from the level of patient satisfaction of 90% in the very satisfied category.   ABSTRAK Tingkat kepuasan pasien terhadap kualitas suatu pelayanan dapat dijadikan indikator  dari kualitas mutu suatu fasilitas kesehatan.  Puskesmas merupakan fasilitas kesehatan  rujukan pertama masyarakat dalam memperoleh pelayanan kesehatan, maka  kualitas mutu  puskesmas harus terjamin. Salah satunya puskesmas Karangayung I. Penelitian ini bertujuan untuk mengetahui tingkat kepuasan pelayanan kefarmasian rawat jalan di Puskesmas Karangayung I dari prespektif pasien. Penelitian ini menggunakan deskriptif kuantitatif dan menggunakan desain cross-sectional. Menggunakan 95 responden yang memenuhi kriteria inklusi dan eksklusi penelitian. Analisis data menggunakan analisis data univariate untuk mengetahui tingkat kepuasan pasien terhadap kualitas pelayanan kefarmasian. Instrumen yang digunakan berupa kuesioner. Hasil penelitian menunjukkan tingkat kepuasan responden pada dimensi ketanggapan (responsiveness) 90,9%, dimensi jaminan (assurance) 91,9%, dimensi perhatian (empathy) 88,8%, dimensi kehandalan (reliability) 91,7% dan dimensi tampilan fisik (tangibles) 86,8%. Mutu pelayanan di Puskesmas Karangayung termasuk bagus, terlihat  dari tingkat kepuasan pasien  sebanyak 90% berada pada kategori sangat puas.